The black elfstone : the fall of Shannara - Brooks, Terry (Brooks, Terry. Fall of Shannara, 2017)
"The first book of the triumphant and epic four-part conclusion to the Shannara series, from one of the all-time masters of fantasy. Across the Four Lands, peace has reigned for generations. But now, in the far north, an unknown enemy is massing. More troubling than the carnage is the strange and wondrous power wielded by the attackers--a breed of magic unfamiliar even to the Druid order. Fearing the worst, the High Druid dispatches a diplomatic party under the protection of the order's sworn guardian, Dar Leah, to confront the mysterious, encroaching force and discover its purpose. But another crucial journey is being undertaken. Exiled onetime High Druid Drisker Arc has been living in quiet seclusion, far from the politics and power struggles of his former life, until two brutal attacks by would-be assassins force him to seek out an infamous murder-for-hire guild--and find the hidden enemy who has marked him for death. At his side is Tarsha Kaynin, a young woman gifted with the wishsong and eager to be schooled in its formidable power by a master. She, too, is pursuing a mission: to locate her wayward brother, whose own magic has driven him to deadly madness and kindled his rage for vengeance against his sister. In their darkest hours, facing dangerous adversaries, the lives and quests of Dar Leah, Drisker Arc, and Tarsha Kaynin will be inextricably drawn together. And the challenges each confronts will have resounding consequences for the future of the Four Lands.--